Profile of Molecular Subtypes of Breast Cancer Among Bangladeshi Women : Audit of Initial Experience - Rahman, Md Zillur; Karim, Anwarul (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Background : Receptor status and molecular subtyping of breast cancers are crucial for patient management.We present here our initial experience on the status of different molecular subtypes and clinicopathological characteristics of invasive breast carcinomas in Bangladeshi population especially in Chittagong zone. Methods : A total of 59 histopathologically confirmed cases of invasive ductal carcinoma were selected for this study. Fifteen out of 59 cases were reported as HER2 equivalent and could not be categorized into any subtype because of the lack of availability of fluorescence in situ hybridization. The remaining 44 cases were distributed into different molecular subtypes and then the clinicopathological characteristics were compared for each molecular subtype. Results : Age ranges from 24-70 years with a mean age of 43.95 years. Most of the patients were in 41-50 years age group. Among the 44 cases, most common subtype was HER2/neu amplification 13 cases (29.55%). Luminal A, luminal B and basal like subtypes were 11 (25%) 10 (22.73%) and 10 (22.73%) respectively. The mean tumor size was 3.46 cm and the highest mean tumor size was in basal like subtype (4.01cm). Twenty five out of 59 cases (42.37%) showed axillary lymph node metastasis. Lowest axillary lymph node metastasis was found in luminal A subtype (3/11=27.27%). Conclusion : HER2/neu amplification subtype was found to be more common in this region. Luminal A subtype was found to be more favorable in comparison to the other subtypes in terms of axillary lymph node metastasis. Chatt Maa Shi Hosp Med Coll J; Vol.16 (2); July 2017; Page 1-4